2001
DOI: 10.1046/j.1464-5491.2001.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungal infection of the diabetic foot: two distinct syndromes

Abstract: Candida spp. is associated with two distinctive patterns of protracted ulceration in diabetic feet which improve following systemic antifungal therapy. Diabet. Med. 18, 567-572 (2001)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 10 publications
3
23
1
Order By: Relevance
“…The fungal profile showed the occurrence of non Candida albicans (NCA) namely Candida glabrata as the predominant yeast isolates followed by Candida albicans, Candida dubliniensis, Candida tropicalis and Candida krusei. The results of the study similar with the studies of Chincholikar and Pal [33]; Heald et al [34] which reported non Candida albicans as the predominant yeast isolates from cases of diabetic foot infections. Bader et al [35] reported that Candida glabrata as the emerging group of non Candida albicans (NCA) as it causes candidemia among diabetic patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The fungal profile showed the occurrence of non Candida albicans (NCA) namely Candida glabrata as the predominant yeast isolates followed by Candida albicans, Candida dubliniensis, Candida tropicalis and Candida krusei. The results of the study similar with the studies of Chincholikar and Pal [33]; Heald et al [34] which reported non Candida albicans as the predominant yeast isolates from cases of diabetic foot infections. Bader et al [35] reported that Candida glabrata as the emerging group of non Candida albicans (NCA) as it causes candidemia among diabetic patients.…”
Section: Discussionsupporting
confidence: 93%
“…So species identification of Candida was essential for successful management [37]. Moreover, candidal infection in diabetic foot was a rare entity and was previously described in five reports by Heald et al [34]; Missoni et al [36]; Yener et al [38]; Chellan et al [8] and Nithyalakshmi et al [9]. Since, our reports confirmed the prevalence of Candida albicans and non albicans in diabetic foot infections along with antifungal susceptibility pattern.…”
Section: Discussionsupporting
confidence: 93%
“…Some authors have attempted to explain the clinical importance of Candida isolations from the diabetic foot ulcers by assessing the healing of lesions through the application of antimycotics [19]. The explanation that we would offer is chemotyping of isolates of the same species of Candida from foot ulcer and interdigital spaces of the same and/or the other foot by using GC method.…”
Section: Discussionmentioning
confidence: 98%
“…Mlinaric Missoni et al from Croatia had reported the fungal incidence in tissue biopsy specimens of 22 diabetic patients who had clinical evidence of fungal infections (12,24). The predominant isolates were C. parapsilosis (45.5%), C. tropicalis (22.7%), C. albicans (9.1%), and C. glabrata (9.1%).…”
Section: Discussionmentioning
confidence: 99%